STUDI FINANCIAL DISTRESS PADA PERUSAHAAN PERBANKAN DI BEI - Theodorus, Stevano; Artini, Luh Gede Sri (E-Jurnal Manajemen; Vol 7 No 5 (2018), 2018)
Financial Distress is a condition where the company unable to fulfill their obligation. Big scale effect on the banking system would cause monetary crisis which leads to economic crisis. This study is meant to analyzed CAMEL(S) ratio predict ing the probability of Financial Distress occured on banks that are listed at IDX 2010-2015 period. This research population are banks that are listed at IDX 2010-2015 period, which there are 30 banks. Samples are taken with purposive sampling which there are 28 banks are being used for further analysis. The method that were taken to analyze are logistic regression. The result of the study showed that only BOPO and ROA are capable significantly to predict the probability of Financial Distress occured on bank . On the otherhand CAR, NPL and log of total asset are unsignificantly to predict the prbability of financial distress.